Breaking the Mould: Alternative approaches to monitoring and evaluatio n - Dillon, Neil (ALNAP, 2019)
This paper looks at a range of M&E innovations that are designed speci fically to provide input to ongoing iterative decision-making and lear ning at the project level. It identifies three key areas for potential innovation: 1) timing of M&E data provision; 2) flexibility of M&E fr ameworks to evolve with programme change; and 3) approaches to integra te diverse perspectives on project implementation in a meaningful way. It then looks at a collection of approaches currently being used in e ach of these three areas through a series of ‘practice examples’, cons idering the key lessons learned. Finally, the paper discusses the majo r opportunities and challenges for applying and scaling up the use of these approaches inside the humanitarian sector.